PENINGKATAN PARTISIPASI DAN KEMANDIRIAN MASYARAKAT DALAM PENANGANAN STUNTING MELALUI PROGRAM DAPUR IBU LURAH - Riska Aprilia Wardani; Nasrul Hadi Purwanto; Eko Agus Cahyono (LPPM Universitas Nusa Mandiri, 2026)
This Community Service activity was motivated by the high prevalence of stunting in Sooko Village, Mojokerto Regency, which is triggered by multidimensional factors including parental ignorance in fulfilling toddler nutrition, economic limitations, and the lack of synergy of sustainable programs among stakeholders at the village level. To address this, a series of activity implementation methods were carried out, including intensive nutrition education on stunting and the preparation of nutritious menus, local food diversification training to optimize affordable food ingredients, and productive skills training such as making herbal products using a food dehydrator and making ecoprint batik using a steaming technique. All methods were designed in a participatory and collaborative manner, involving the village government, health workers, and PKK members as participants, with direct mentoring from a team of academics to ensure the achievement of applicable and sustainable knowledge and skills transfer. This community service activity has been successfully implemented through a series of collaborative interventions between the village government, health workers, and academics in Sooko Village, Mojokerto Regency. The implementation results showed a significant increase in community capacity, including a 40% increase in nutritional knowledge, mastery of herbal product production skills (using a food dehydrator) and ecoprint batik by 100% of participants, and the establishment of a Healthy Fund mechanism from the allocation of group business profits to purchase nutritious food for stunted toddlers. Sustainable synergy between nutrition training, economic empowerment, and local policy support can be an effective blueprint for accelerating the reduction in stunting prevalence independently and sustainably.